2014
DOI: 10.1093/jjco/hyu027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HMB/Arg/Gln on the Prevention of Radiation Dermatitis in Head and Neck Cancer Patients Treated with Concurrent Chemoradiotherapy

Abstract: Our study indicated that beta-hydroxy-beta-methylbutyrate/arginine/glutamine supplementation was potentially effective in the prevention of radiation dermatitis in head and neck cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 28 publications
0
37
0
1
Order By: Relevance
“…A previous study reported that β-hydroxy-β-methylbutyrate/arginine/glutamine supplementation was potentially effective in the prevention of radiation dermatitis in patients with HNC, as this supplementation was a protective nutrient with anti-inflammatory effects favoring the healing of inflammatory skin wounds (34).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that β-hydroxy-β-methylbutyrate/arginine/glutamine supplementation was potentially effective in the prevention of radiation dermatitis in patients with HNC, as this supplementation was a protective nutrient with anti-inflammatory effects favoring the healing of inflammatory skin wounds (34).…”
Section: Discussionmentioning
confidence: 99%
“…A compounding agent containing HMB, glutamine, and arginine effectively protected against chemoradiotherapyinduced dermatitis in head and neck cancer patients (29). This effect may be related to the anti-inflammatory activity of HMB.…”
Section: Discussionmentioning
confidence: 85%
“…Embora essa associação terapêutica seja bené ca na terapia antineoplásica, ela pode aumentar a incidência e a severidade de reações adversas -como a radiodermatite -, sendo importante seu manejo adequado e considerando os impactos negativos das reações no tratamento e na qualidade de vida do paciente 2 .…”
Section: Introductionunclassified